Lessons from World Bank Research on Financial Crises - World Bank (Washington, DC: World Bank, 2012)
The benefits of financial development and globalization have come with continuing fragility in financial sectors. Periodic crises have had real but heterogeneous welfare impacts and not just for poor people; indeed, some of the conditions that foster deep and persistent poverty, such as lack of connectivity to markets, have provided a degree of protection for the poor. Past crises have also had longer-term impacts for some of those affected, most notably through the nutrition and schooling of children in poor families. As in other areas of policy, effective responses to a crisis require sound data and must take account of incentives and behavior. An important lesson from past experience is that the short-term responses to a crisis-macroeconomic stabilization, trade policies, financial sector policies and social protection-cannot ignore longer-term implications for both economic development and vulnerability to future crises.